Functional outcome in displaced proximal humeral fractures in adults treated by proximal humeral locking plates - Narasimha Rao, N. V.; Kanth, K. Ravi; Yasam, Rama Priya; Chandra, T. Jaya (International Journal of Research in Orthopaedics, 2019)
Background: The management of proximal humerus fractures (PHF) is a challenging task to any surgeon. Study was conducted to evaluate the clinical and functional outcome of the proximal humeral internal locking system in fixation of displaced proximal humeral fractures. Methods: Study was conducted in the Department of Orthopedics, GSL Medical College. Informed written consent was taken from the study participants. All skeletally mature patients aged >18 years, presenting with displaced PHF according to Neer two, three and four part fracture were included in the study. Either deltopectoral or deltoid splitting approach was used for surgery, post-operative rehabilitation was started on day one. Results: Twenty-five patients with PHF were enrolled in the study; five-holed proximal humerus locking plate (PHLP) was used for 18 patients, eight-holed PHLP for 05 and three-holed, ten-holed PHLP for 01 for one each. The Constant-Murley score was significantly improved (p=0.000) over each successive follow-up period with the average improvement of around 19 scores between 1st and 2nd follow-up and around 15 score improvement between 2nd and 3rd follow-up. Conclusions: The proximal humeral locking plate is an adequate device for the fixation of displaced two-part, three-part and four-part PHF. Patient can regain good shoulder function, resume normal activities much earlier.